Energy Infiltration Effect and Energy Body – a Unique Criterion for Building Thermal Insulation - Piotr BIERANOWSKI (Problemy Mechatroniki, 2022)
This publication is provided with the author’s suggestions regarding modification of the basic criterion – heat transfer coefficient. According to the author, the basic criterion of building thermal protection should be extended in such a manner that it will be simple and easy to evaluate a building’s capacity to recover thermal energy accumulated in the wall structure.